(untitled) (Bangladesh Journal of Botany, 2025)
Gluten-free food products are becoming popular due to increased consumers awareness on celiac disease. The present investigation was undertaken to develop gluten free cookies from composite flour consisting of germinated brown rice and oat flour with better nutritional and sensory characteristics. Cookies were prepared using germinated brown rice and oats flour to make different treatment combinations. The developed products were packed in aluminium laminates and stored under ambient conditions for a period of 90 days. The proximate analysis of cookies revealed that among proximate constituents, highest mean crude protein of 8.58% was recorded in T7 . With the progression of storage period crude fibre content decreased from 1.59 to 1.26%. Bangladesh J. Bot. 54(3): 627-630, 2025 (September)